2022
DOI: 10.1021/jacs.2c01857
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis inside Single Activated Phagolysosomes: Quantitative and Selective Measurements of Submillisecond Dynamics of Reactive Oxygen and Nitrogen Species Production with a Nanoelectrochemical Sensor

Abstract: Reactive oxygen and nitrogen species (ROS/RNS) are generated by macrophages inside their phagolysosomes. This production is essential for phagocytosis of damaged cells and pathogens, i.e., protecting our organism and maintaining immune homeostasis. The ability to quantitatively and individually monitor the four primary ROS/RNS (ONOO -, H2O2, NO, and NO2 -) with sub-millisecond resolution is clearly warranted to elucidate the still unclear mechanisms of their rapid generation and to track their concentrations v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…[ 11‐16 ] Microelectrode or nanoelectrode with high temporal‐spatial resolution can be positioned near or inside individual cells to monitor single cell behaviors ( e.g ., exocytosis) [ 17‐21 ] or subcellular processes ( e.g ., intracellular events). [ 22‐28 ] These achievements greatly promote the understanding of cellular metabolism, cell‐cell communication and cell‐matrix interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11‐16 ] Microelectrode or nanoelectrode with high temporal‐spatial resolution can be positioned near or inside individual cells to monitor single cell behaviors ( e.g ., exocytosis) [ 17‐21 ] or subcellular processes ( e.g ., intracellular events). [ 22‐28 ] These achievements greatly promote the understanding of cellular metabolism, cell‐cell communication and cell‐matrix interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemistry with high spatiotemporal resolution has been widely applied in monitoring neurochemicals released in biological and pathological systems continuously and rapidly. [22][23][24][25] To date, electrochemical sensing of H 2 S can be realized through both amperometry and potentiometry. For example, Hu et al developed a 3D porous structure to detect H 2 S released from single HeLa cells with amperometric methods.…”
mentioning
confidence: 99%
“…Similar to reactive oxygen species (ROS), reactive nitrogen species (RNS) are considered to be another physiological regulatory species for inducing damage to biomacromolecules (i.e., lipids, proteins, and DNA) through enhanced nitrosative stress. Nitrosative stress is a biological process derived from the biochemical interaction of nitric oxide (NO) or NO-derived RNS with ROS, which plays a key role in the pathophysiology of various diseases, such as myocardial ischemic reperfusion injury, atherosclerosis, heart failure, hypertension, etc. Intracellular nitrosative stress is mainly the result of the rate of RNS production exceeding the neutralization capacity of cells, which induces intracellular protein tyrosine nitration through the peroxynitrite (ONOO – ), nitrite, hydrogen peroxide, or peroxidase pathways, resulting in a series of cellular damage. Recently, Bu et al reported an electrophilic zeolitic imidazole framework electrophilic (ZIF-82-PVP) for releasing nitrite to suppress autophagy and enhance nitrosative stress-mediated hypoxic prostate cancer therapy . Among reported radical species, ONOO – , derived from the diffusion-limited reaction of superoxide (O 2 •– ) with NO, is the most potential oxidizing and nitrating inducer of cell apoptosis. The resulting ONOO – appears to be much more toxic than ROS, including hydroxyl radicals .…”
mentioning
confidence: 99%